2008
DOI: 10.1021/es702657n
|View full text |Cite
|
Sign up to set email alerts
|

Field Trial and Modeling of Uptake Rates of In Situ Lipid-Free Polyethylene Membrane Passive Sampler

Abstract: Lipid-free polyethylene membrane tubing (LFT) has been further developed in response to a growing need for an inexpensive and simple time-integrative sampling device for dissolved hydrophobic contaminants in water. The LFT sampler is based on the diffusion of dissolved hydrophobic target compounds through the aqueous boundary layer and into the polyethylene membrane, mimicking uptake by organisms. We demonstrate through laboratory and field validation studies that LFT provided the same benefits as many other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 31 publications
0
64
0
Order By: Relevance
“…Initially, silicone extraction and pre-cleaning experiments used ethyl acetate since it does not severely impact the integrity of the silicone itself (Rusina et al, 2007), and ethyl acetate is a solvent with both polar and non-polar properties that might be conducive to OPAHs. In addition, to exploit inherent differences in each polymer, ethyl acetate was used as the primary solvent for silicone, while the more non-polar hexane was used for LDPE cleaning as previously described (Anderson et al, 2008). Pre-cleaning experiments for silicones were adapted from several studies (Booij et al, 2002; Rusina et al, 2007; Yates et al, 2007; Allan et al, 2009; Schafer et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, silicone extraction and pre-cleaning experiments used ethyl acetate since it does not severely impact the integrity of the silicone itself (Rusina et al, 2007), and ethyl acetate is a solvent with both polar and non-polar properties that might be conducive to OPAHs. In addition, to exploit inherent differences in each polymer, ethyl acetate was used as the primary solvent for silicone, while the more non-polar hexane was used for LDPE cleaning as previously described (Anderson et al, 2008). Pre-cleaning experiments for silicones were adapted from several studies (Booij et al, 2002; Rusina et al, 2007; Yates et al, 2007; Allan et al, 2009; Schafer et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Individual silicone strips were extracted with two sequential rounds of 100 mL of ethyl acetate on an orbital shaker set at 60 rpm (ambient temperature), and the total extraction time was 18 hours. LDPE was extracted with hexanes in a similar fashion (Anderson et al, 2008). All extracts were quantitatively concentrated to 1 mL using closed cell evaporators (TurboVaps ® , Biotage, Charlotte, NC), and transferred to chromatography vials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher adsorption capacity for HOCs of A-HA than natural humic substances has been attributed to its lower O/C ratio which makes A-HA a less hydrophilic material with lower carbohydrate and carboxyl contents (Chiou et al, 1987;McCarthy et al, 1989). The C free has been often related to bioavailability of HOCs in natural waters (Anderson et al, 2008;Hu et al, 2009;Cui et al, 2013;Yang et al, 2007). However, recent studies showed that the bioavailable fraction of HOCs in DOM-containing water may also encompass the reversible desorption portion of DOM-sorbed chemical (Chen et al, 2008).…”
Section: Accessible Concentrations and Accessibilitymentioning
confidence: 99%
“…Low-density polyethylene (LDPE) is a widely-used material for making passive samplers (Anderson et al, 2008). When LDPE is deployed in water, hydrophobic organic contaminants (HOCs) diffuse into LDPE from the water into the hydrophobic polymer.…”
Section: Introductionmentioning
confidence: 99%